Implementasi Modul Ajar di Sekolah SMAN 4 Palangkaraya - Yuwantri Yuwantri; Jessica Putri Manuella; Lelo Lelo (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This study aims to implement and evaluate the effectiveness of a learning module designed for X grade students (Phase E) at SMAN 4 Palangkaraya, focusing on the Christian values of love, justice, and tolerance within the framework of the Merdeka Curriculum. The implementation involved classroom teaching using lectures, group discussions, and quizzes to foster active and meaningful learning experiences. The objectives included ensuring students' understanding of the core values, developing their ability to articulate these values, and achieving a minimum score on quizzes. The methodology included direct teaching, observation of student responses and engagement, and evaluation of learning outcomes through cognitive and affective assessments. Findings revealed that 90% of students actively participated in discussions, and all groups engaged in answering quiz questions. The use of rewards notably enhanced student enthusiasm and participation. Despite the overall success, some students did not achieve the highest performance level. The implications suggest that integrating technology into the learning process and thorough preparation of teaching materials are crucial for enhancing student outcomes. This study contributes to the understanding of how Christian values can be effectively integrated into the curriculum to promote holistic student development, aligning with the Pancasila Student Profile, which emphasizes faith, moral integrity, global diversity, and collaboration.